Use of verb-noun collocations in spoken and written discourse of foreign learners in Iran - Bazzaz, Fatemeh Ebrahimi (2013)
The present study tries to explore the knowledge and the use of verb-noun collocations in spoken and written discourse of English as foreign language (EFL) learners in Iran. In addition, the current study aims at examining and describing possible correlation and the differences in knowledge and use of verb-noun collocations among four groups of Iranian EFL learners representing four academic years (freshman, sophomore, junior, and senior). The study also qualitatively examines the factors that influence Iranian EFL students’ use of verb-noun collocations. The participants in this study comprised of four groups of 212 male and female English students according to their academic years in the Department of English Translation, at the Islamic Azad University, Tehran North Branch (IAUTNB) in Tehran, Iran. Data was collected by two tests: a Cloze Test, and a collocation test, and a series of six pictures for writing and speaking. The Test of Collocation was a C-Test in which there were 50 items. Each item measured a collocation from which the verb was deleted except the first letter/phoneme. This test was employed to measure students’ knowledge of collocations. The Cloze Test, which has 25 blanks, was utilised to measure students’ general language proficiency. To measure the use of verb-noun collocations in written discourse, there was a 60-minute task of writing story based on a series of six pictures whereby for each picture, three verb-noun collocations were measured,and nouns were provided to limit the choice of collocations. To assess the use of verb-noun collocations in spoken discourse, a 30-minute task of speaking was conducted in the laboratory in which for each picture three verb-noun collocations were measured, but nouns were not provided to observe whether participants could use them correctly. To test the research hypotheses, Pearson moment correlation and ANOVA were employed. Results of Pearson’s correlation [r = .532, n = 212, p <0.01] for the first research question showed that there was a high correlation between the students’ verb-noun collocational knowledge and their overall language proficiency. Moreover, the results of the statistical analysis of ANOVA for the second research question showed that there was a significant difference in the knowledge of lexical verb-noun collocations, both between and within the four academic years, F (3, 208) = 20,637 at the p <0.0001 level which is much less than α ≤ 0.05. The results of the statistical analysis of ANOVA for the third research question showed that there was a significant difference in the use of lexical verb-noun collocations in written discourse both between and within the four academic years, F (3,208) = 21.603 at the p <0.0001 level which is much less than α ≤ 0.05 for written discourse. The results of the statistical analysis of ANOVA for the fourth research question showed that there was a significant difference in the use of lexical verb-noun collocations in spoken discourse F (3,208) = 17.498 at the p <0.0001 level which is much less than α ≤ .05. Similarly, results of Pearson’s product correlation [r = .932, n = 212, p <0.01] for the fifth research question showed that there was a strong correlation between the students’ use of collocations both in spoken and written discourse. This finding indicates that Iranian students may have the collocational knowledge to use collocations correctly in both spoken and written discourse. The qualitative inquiry for the sixth research question revealed that accurate usage of verb-noun collocations could be related to cultural factors, semantic factors, and positive and negative transfer. The findings also suggest that cultural bound verb-noun collocations can be emphasised in order to assist Iranian students to overcome errors in use due to differences in Iranian and Western cultures.